The emancipatory inclusion of nonhuman animals in the Dutch sustainable food system transition: An embodied critical discourse analysis - Anne van Veen; Ingrid Visseren-Hamakers (Earth System Governance)
There is increasing agreement among scientists and policy makers that we need transformative change, change at the deepest levels of society, to become sustainable. There is also increasing attention for politics, power relations and justice in studying and governing sustainability transitions. This attention has however largely been limited to human politics, power relations and justice, even though other animals are also stakeholders in these transitions. This article focuses on the inclusion of nonhuman animals in the food system transition in the Netherlands. Through an embodied critical discourse analysis of academic papers and policy texts we show that there is a lack of inclusion of other animals as stakeholders, and how anthropocentric ontological and epistemological assumptions lead to reproducing power inequalities and the perpetuation of practices of nonhuman animal exclusion and oppression. In addition, our analysis demonstrates how terms such as ‘intrinsic value’ serve human rather than nonhuman interests because they are interpreted in such a way that they simultaneously assuage guilt and legitimize continued owning and killing of other animals by humans. We also contribute methodologically by adding the practice of re-embodiment of texts to the close reading method generally used in Critical Discourse Analysis, thereby making this method less anthropocentric. Finally, we propose steps towards the emancipatory inclusion of nonhuman animals in environmental governance.